1999
DOI: 10.1046/j.1365-2958.1999.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

The R28 protein of Streptococcus pyogenes is related to several group B streptococcal surface proteins, confers protective immunity and promotes binding to human epithelial cells

Abstract: SummaryThe R28 protein is a surface molecule expressed by some strains of Streptococcus pyogenes (group A streptococcus). Here, we present evidence that R28 may play an important role in virulence. Sequence analysis demonstrated that R28 has an extremely repetitive sequence and can be viewed as a chimera derived from the three surface proteins Rib, a and b of the group B streptococcus (GBS). Thus, the gene encoding R28 may have originated in GBS. The R28 protein promotes adhesion to human epithelial cells, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
187
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(200 citation statements)
references
References 51 publications
(105 reference statements)
12
187
0
1
Order By: Relevance
“…Virtually nothing is known about molecular mechanisms in puerperal fever, but an epidemiological study in Britain showed that the surface protein R28 was common among S. pyogenes strains isolated from recent outbreaks of puerperal fever, but was found in only a minority of pharyngitis strains [23]. This over-representation of R28-expressing strains among puerperal fever isolates led us to hypothesize that the R28 protein played an important role in the epidemics of puerperal fever [24]. For obvious reasons, S. pyogenes isolates from the 18 th and 19 th century epidemics of puerperal fever were not available for characterization, but analysis of cases of puerperal fever reported in the litterature in which the S. pyogenes strains were serotyped supported the hypothesis that R28-expressing strains were overrepresented also among puerperal fever isolates recovered earlier in the 20 th century [24].…”
Section: Puerperal Fever and The R28 Proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…Virtually nothing is known about molecular mechanisms in puerperal fever, but an epidemiological study in Britain showed that the surface protein R28 was common among S. pyogenes strains isolated from recent outbreaks of puerperal fever, but was found in only a minority of pharyngitis strains [23]. This over-representation of R28-expressing strains among puerperal fever isolates led us to hypothesize that the R28 protein played an important role in the epidemics of puerperal fever [24]. For obvious reasons, S. pyogenes isolates from the 18 th and 19 th century epidemics of puerperal fever were not available for characterization, but analysis of cases of puerperal fever reported in the litterature in which the S. pyogenes strains were serotyped supported the hypothesis that R28-expressing strains were overrepresented also among puerperal fever isolates recovered earlier in the 20 th century [24].…”
Section: Puerperal Fever and The R28 Proteinmentioning
confidence: 99%
“…This over-representation of R28-expressing strains among puerperal fever isolates led us to hypothesize that the R28 protein played an important role in the epidemics of puerperal fever [24]. For obvious reasons, S. pyogenes isolates from the 18 th and 19 th century epidemics of puerperal fever were not available for characterization, but analysis of cases of puerperal fever reported in the litterature in which the S. pyogenes strains were serotyped supported the hypothesis that R28-expressing strains were overrepresented also among puerperal fever isolates recovered earlier in the 20 th century [24]. Although many S. pyogenes strains isolated from 20 th century cases of puerperal fever probably did not express R28, this finding does not contradict the hypothesis that R28 may favor the emergence of epidemics, because endemic isolates, that cause sporadic cases or small outbreaks, would be expected to be non-clonal, while only epidemic strains would be expected to be clonal [25].…”
Section: Puerperal Fever and The R28 Proteinmentioning
confidence: 99%
See 3 more Smart Citations